Monocular elevation paresis and contralateral downgaze paresis from unilateral mesodiencephalic infarction. - Wiest, G (1996)
A 26 year old woman presented with monocular elevation paresis of the right eye, contralateral paresis of downward gaze, and subtle bilateral ptosis. Magnetic resonance imaging disclosed a unilateral embolic infarction restricted to the mesodiencephalic junction involving the left paramedian thalamus. Preserved vertical oculocephalic movements and intact Bell's phenomenon suggested a supranuclear lesion. This rare "crossed vertical gaze paresis" results from a lesion near the oculomotor nucleus affecting ipsilateral downward gaze and contralateral upward gaze fibres, originating in the rostral interstitial nucleus of the medial longitudinal fasciculus (riMLF).